Investigation of associations of ARMS2, CD14, and TLR4 gene polymorphisms with wet age-related macular degeneration in a Greek population - Sarli A (Dove Medical Press, 2017)
Antonia Sarli,1 Iosif Skalidakis,2 Aliki Velissari,1 Chryssanthi Koutsandrea,2 Maria Stefaniotou,3 Michael B Petersen,4,5 Christos Kroupis,1,* George Kitsos,3,* Marilita M Moschos2,* 1Department of Clinical Biochemistry, Attikon University General Hospital, 21st Department of Ophthalmology, “G. Gennimatas” General Hospital, Medical School, National and Kapodistrian University of Athens, Athens, 3Department of Ophthalmology, Ioannina University General Hospital, University of Ioannina, Ioannina, Greece; 4Department of Clinical Genetics, Aalborg University Hospital, Aalborg, Denmark; 5Department of Clinical Medicine, Aalborg University Hospital, Aalborg, Denmark *These authors contributed equally to this work Background: Age-related macular degeneration (AMD) is a multifactorial degenerative ocular disease that leads to loss of central vision. Functional gene polymorphisms have already been associated with the disease (for example, ARMS2 A69S, rs10490924).Aim: The goal of our study was to verify the correlation of the aforementioned ARMS2 variation with the disease, to examine, for the first time, the role of the CD14 C260T variation (rs2569190), and to investigate the association of two TLR4 polymorphisms (Asp299Gly or rs4986790 and Thr399Ile or rs4986791) in a Greek population with the wet form of AMD.Patients and methods: Genomic DNAs were isolated from blood samples of 103 healthy controls and 120 Greek patients with wet AMD who were age- and sex-matched, and all of whom were clinically evaluated. For the genotyping of all selected polymorphisms, polymerase chain reaction–restriction fragment length polymorphism analysis was performed.Results and conclusions: This study confirmed the association between the ARMS2 variation and AMD, detecting the T risk allele in a significantly higher frequency in the patient group, compared with the control subjects (45% vs 29.13%, P<0.001, odds ratio [OR] 1.99, confidence interval 1.34–2.95). For the CD14 polymorphism, no statistically significant correlation was observed. As for the TLR4 polymorphisms, the percentage of heterozygotes increased from 2.9% to 11.7% in the patient population for Asp299Gly and from 1.9% to 10% for the Thr399Ile polymorphism (ORs 4.40 [P=0.01] and 5.61 [P=0.0088], respectively). Although our ARMS2 and CD14 results provided definite conclusions, the role of innate immunity TLR4 gene awaits further investigation in larger AMD populations with more clinical data collected on past microbial infections. Keywords: AMD, ARMS2, CD14, TLR4, SNPs, PCR-RFLP